TINJAUAN LITERATUR SISTEMATIK TENTANG KESEHATAN MENTAL SISWA DI SEKOLAH DASAR - Wuladari, Citra; Haifaturrahmah, Haifaturrahmah; Nizaar, Muhammad (Jurnal Ilmiah Telaah, 2026)
Mental health in primary schools is important to know. This study aims to 1) identify mental health in primary schools; 2) identify mental health factors in primary schools; and 3) analyze published articles (objectives,methods and research results) in scientific journals for the period 2010-2022 that are relevant to mental health in primary schools. This study used a systematic literature review method with all articles found which were then selected according to the inclusion, exclusion and quality assessment criteria. The resulting 36 scientific articles can be analyzed in accordance with the research questions that have been set. The results of the study are in the form of a description of mental health in elementary schools which has not been widely discussed by previous studies including the factors that influence it, the methods or techniques used and research trends during the period 2010 -2022. This research has implications for the discovery of future research that can be used as an initial foothold for future researchers who have an interest in the theme of research on mental health in elementary schools.